Draft Genome Sequences of Two Bacillus thuringiensis Strains and Characterization of a Putative 41.9-kDa Insecticidal Toxin - Leopoldo Palma; Delia Muñoz; Colin Berry; Jesús Murillo; Primitivo Caballero (Toxins, 2014)
In this work, we report the genome sequencing of two Bacillus thuringiensis strains using Illumina next-generation sequencing technology (NGS). Strain Hu4-2, toxic to many lepidopteran pest species and to some mosquitoes, encoded genes for two insecticidal crystal (Cry) proteins, cry1Ia and cry9Ea, and a vegetative insecticidal protein (Vip) gene, vip3Ca2. Strain Leapi01 contained genes coding for seven Cry proteins (cry1Aa, cry1Ca, cry1Da, cry2Ab, cry9Ea and two cry1Ia gene variants) and a vip3 gene (vip3Aa10). A putative novel insecticidal protein gene 1143 bp long was found in both strains, whose sequences exhibited 100% nucleotide identity. The predicted protein showed 57 and 100% pairwise identity to protein sequence 72 from a patented Bt strain (US8318900) and to a putative 41.9-kDa insecticidal toxin from Bacillus cereus, respectively. The 41.9-kDa protein, containing a C-terminal 6× HisTag fusion, was expressed in Escherichia coli and tested for the first time against four lepidopteran species (Mamestra brassicae, Ostrinia nubilalis, Spodoptera frugiperda and S. littoralis) and the green-peach aphid Myzus persicae at doses as high as 4.8 µg/cm2 and 1.5 mg/mL, respectively. At these protein concentrations, the recombinant 41.9-kDa protein caused no mortality or symptoms of impaired growth against any of the insects tested, suggesting that these species are outside the protein’s target range or that the protein may not, in fact, be toxic. While the use of the polymerase chain reaction has allowed a significant increase in the number of Bt insecticidal genes characterized to date, novel NGS technologies promise a much faster, cheaper and efficient screening of Bt pesticidal proteins.